Rola menedżera personalnego w przedsiębiorstwie międzynarodowym - Kopeć, Jacek (The role of a personnel manager in an international company, 2006)
The first part of the paper presents international context of human resource management (HRM). The main aim is to focus on the organization of human resources in an international corporation. Characteristic features of the organizational context of HRM were presented in the next part. The author discusses personnel manager’s tasks and roles. The profile includes the following roles: strategic partners, administrative expert, employee spokesman, change agent, master of globalization, architect of knowledge management and constructor of talent management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 45-52